Reduction of Nitroarenes to Anilines with a Benzothiazoline: Application to Enantioselective Synthesis of 2-Arylquinoline Derivatives - Miyagawa, Masamichi; Yamamoto, Ryota; Kobayashi, Nanako; Akiyama, Takahiko (Synlett, 2019)
The metal-free reduction of nitroarenes to aniline derivatives was accomplished in a short time by using a benzothiazoline as the hydrogen donor in combination with a Brønsted acid. An enantioselective synthesis of 2-arylquinolines was achieved by using 1-aryl-3-(2-nitrophenyl)propan-1-ones as starting materials and a combination of a benzothiazoline and a chiral phosphoric acid.
Keywords: benzothiazolines; phosphoric acids; isoquinolines; nitroarenes; anilines; reduction